2018
DOI: 10.3390/md16060192
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Atypical PKC-Iota Inhibitor, Echinochrome A, Enhances Cardiomyocyte Differentiation from Mouse Embryonic Stem Cells

Abstract: Echinochrome A (EchA) is a marine bioproduct extracted from sea urchins having antioxidant, antimicrobial, anti-inflammatory, and chelating effects, and is the active component of the clinical drug histochrome. We investigated the potential use of Ech A for inducing cardiomyocyte differentiation from mouse embryonic stem cells (mESCs). We also assessed the effects of Ech A on mitochondrial mass, inner membrane potential (Δψm), reactive oxygen species generation, and levels of Ca2+. To identify the direct targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The antimicrobial mechanism of echinochrome has not been completely resolved, but evidence suggests its production of hydrogen peroxide and/or iron chelation, abates microbial proliferation, ( Coates et al, 2018 ; Lebedev et al, 2005 ; Perry and Epel, 1981 ). All of these studies agree that sea urchin pigments have anti-microbial activity, and that these small molecules may also contribute to states of cell physiology and gene expression ( Jeong et al, 2014 ; Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 60%
“…The antimicrobial mechanism of echinochrome has not been completely resolved, but evidence suggests its production of hydrogen peroxide and/or iron chelation, abates microbial proliferation, ( Coates et al, 2018 ; Lebedev et al, 2005 ; Perry and Epel, 1981 ). All of these studies agree that sea urchin pigments have anti-microbial activity, and that these small molecules may also contribute to states of cell physiology and gene expression ( Jeong et al, 2014 ; Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 60%
“…They investigated the potential use of Echinochrome A as an aPKC specific inhibitor and found that IC 50 for PKC-ι is 107 μM under in-vitro kinase assay conditions. Molecular docking simulation results suggested a direct binding of Echinochrome A with PKC-ι [89].…”
Section: Author Detailsmentioning
confidence: 96%
“…Echinochrome A, a naphthoquinoid pigment from sea urchins [157] that inhibits PKCɩ promoted mouse embryonic stem cells differentiation into cardiomyocytes [158]. In vitro kinase assays using echionochrome A also reported decreased activity of PKCδ (IC 50 = 107 μM).…”
Section: Atypical Pkcs As Therapeutic Targetmentioning
confidence: 99%